Expressões faciais de brasileiros e portugueses: sotaques não-verbais? - Motta, Tammy Andrade (2015)
In this work we investigate the phenomenon of non-verbal accents in Portuguese and Brazilian, testing hypotheses about their role in human communication in an attempt to integrate adaptive and social interpretations. This is an experimental study for which were drawn up two stimuli groups: one containing 16 photographs of posed expressions and another containing six photographs of assembled expressions, built by moving specific facial muscles. We asked participants which emotion was being expressed, which was the model's nationality and how much would he be willing to cooperate with the model. A total of 218 individuals of both nationalities (M = 25.82, 64.2% female) participated. Our findings are: (1) pointing to the recognition of nationality through facial expressions, indicating that the human face is capable of providing clues about cultural aspects and supporting the hypothesis of non-verbal accents. Thus, it is possible that expressions of emotion carry information beyond that conveyed by permanent differences in facial physiognomy, appearance or static characteristics; (2) Overall there was no influence of emotion on recognition of nationality, on the other hand, when we emphasize the particularities of each group we observed that the Portuguese have allocated over the emotions of joy and disgust to Brazilians and of sadness and surprise to the Portuguese themselves. Thus, although the term appears to have had no influence on the judgment of nationality in general, few preconceived ideas about the expressiveness of a group may have influenced the granting of citizenship; (3) We also confirm the hypothesis of universal recognition of expressions of emotion, with minor variations which were also observed by other authors. The fear expression had the lowest rate, followed by Sadness and Surprise expressions, Disgust and Joy had the highest frequency; (4) We realize that there is influence of methodological choices on the appearance of differences between men and women in the recognition of facial expressions of emotion, showing that these differences can be attributed to the drawing up and presentation of stimuli; (5) Our results also indicate that positive emotions evoke higher levels of interaction and cooperation. To Brazilian and Portuguese there was a greater willingness to cooperate/interact on average with models expressing joy and lower disposition toward models expressing disgust. Our findings are to support an interactionist interpretation of facial expressions of emotion, which could be further explored in future studies. The chances of universality (supported by evolutionary psychology) and of non-verbal accents (with greater attention to cultural aspects) do not seem to be incompatible but complementary. It may be possible to establish a dialogue to understand how a selected trait becomes individualized.